Vertical Growth of 2D Covalent Organic Framework Nanoplatelets on a Macroporous Scaffold for High-Performance Electrodes - Jiang, Yanqiu (Advanced materials (Deerfield Beach, Fla.), 2022)
© 2022 Wiley-VCH GmbH.